2012
DOI: 10.1017/jfm.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Richtmyer–Meshkov growth of solid and liquid metals in vacuum

Abstract: We present experimental results supporting physics-based ejecta model development, where our main assumption is that ejecta form as a special limiting case of a Richtmyer–Meshkov (RM) instability at a metal–vacuum interface. From this assumption, we test established theory of unstable spike and bubble growth rates, rates that link to the wavelength and amplitudes of surface perturbations. We evaluate the rate theory through novel application of modern laser Doppler velocimetry (LDV) techniques, where we coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(97 citation statements)
references
References 26 publications
5
91
0
1
Order By: Relevance
“…This is observed in liquid release states where the freesurface velocity is seen to jump from zero to u f s and hold steady: it is liquid and retains no significant residual material strength. Because the Sn experiment was shocked to P SB 19.5 GPa, the Sn velocimetry falls within this category: an unremarkable result showing only asymptotic bubble, spike, and free-surface velocities -u b , u ∞ s , and u f s (see [14] ; all measured velocities are known to within 0.01 to 0.02 mm/μs. In the table, the late time measured bubble velocitiesη b,m are reported (in a negative sense) relative to u f s .…”
Section: Approach Data and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is observed in liquid release states where the freesurface velocity is seen to jump from zero to u f s and hold steady: it is liquid and retains no significant residual material strength. Because the Sn experiment was shocked to P SB 19.5 GPa, the Sn velocimetry falls within this category: an unremarkable result showing only asymptotic bubble, spike, and free-surface velocities -u b , u ∞ s , and u f s (see [14] ; all measured velocities are known to within 0.01 to 0.02 mm/μs. In the table, the late time measured bubble velocitiesη b,m are reported (in a negative sense) relative to u f s .…”
Section: Approach Data and Discussionmentioning
confidence: 99%
“…GPa. Application of PTW [13] to the η 0 k = 0.35 Cu gives an average spatial and temporal stress over the spike growth of 0.57 GPa [14].…”
Section: Approach Data and Discussionmentioning
confidence: 99%
“…In the past decades, hydrodynamic simulations have allowed to understand a great part of this phenomenon, and, for example, it has been shown that the amount of ejected material can be linked to the shape of the defects. 2,3 But if one is interested in predicting the characteristics of the ejected particles, microscopic scale seems to be the good scale to focus on. As an example, in case where the defects are parallel grooves, Durand et al have recently used Molecular Dynamic (MD) simulations of large systems to show that the ejection process is as follows: (i) the ejected material forms sheets of liquid metal which go thinner and thinner; (ii) when sheets are sufficiently thin, holes appear and sheets break to form filaments; and (iii) those filaments stretch and finally break also to form spherical clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Material strength also inhibits the growth of the jets (Fig. 2a), which reach more rapidly an asymptotic velocity, smaller than in the hydrodynamic case [5]. A rough overall consistency is found between FE and SPH calculations.…”
Section: Comparisons Between Experiments Theory and Simulationsmentioning
confidence: 62%
“…The first one is based on a hydrodynamic analysis of two-dimensional (2D) wave propagation [3], introducing new variables like the deviation angle φ behind the front (either shock or release), coupled with a geometrical, steadystate description of wedge-shaped charges [4] assuming incompressible fluid behavior. The second approach is the Richtmeyer-Meshkov instability (RMI) theory, which was originally developed to address the spikes forming at the shock-loaded interface between two fluids of different densities, then was successfully used to treat jetting from periodical defects [5,6]. Here, this theory is applied to a single sinusoidal groove (approaching the triangular shape), assuming non-linear growth in a compressible solid with or without accounting for its elasto-plastic behavior.…”
Section: Experiments and Theorymentioning
confidence: 99%